1998
DOI: 10.1007/pl00009010
|View full text |Cite
|
Sign up to set email alerts
|

Production of extracellular lipase by Candida cylindracea CBS 6330

Abstract: In this study we investigated the in¯uences of aeration, substrate type and concentration on extracellular lipase production in a batch fermentor. The use of air enriched with pure oxygen is the most suitable for the lipase production. Additionally, we found that the presence of fats in the culture broth did not affect the value of the volumetric mass transfer coef®cient of oxygen in our system. Olive oil or oleic acid was used as carbon sources. In both cases, the maximal speci®c rate of growth, l max , was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…Increases in k L a to 50 and 83 h −1 resulted in a reduction in biomass concentrations (6.5 and 7.4 g/L, respectively), when compared with what was seen at a k L a of 38 h −1 , probably attributable to the toxic effects of oxygen. It has been demonstrated that an excess of dissolved oxygen may limit cell growth and, consequently, lipase production [28]. Similar behavior was reported in a study of Candida rugosa growing in a bioreactor at different aeration rate conditions, when the highest cell concentration (6.0 g/L) and lipase production (1,800 U/L) were obtained for aeration rates of 3.0 L air/min, with a sharp reduction in both when the aeration rate was up to 4.0 L air/min [29].…”
Section: Influence Of Oxygen Transfermentioning
confidence: 99%
“…Increases in k L a to 50 and 83 h −1 resulted in a reduction in biomass concentrations (6.5 and 7.4 g/L, respectively), when compared with what was seen at a k L a of 38 h −1 , probably attributable to the toxic effects of oxygen. It has been demonstrated that an excess of dissolved oxygen may limit cell growth and, consequently, lipase production [28]. Similar behavior was reported in a study of Candida rugosa growing in a bioreactor at different aeration rate conditions, when the highest cell concentration (6.0 g/L) and lipase production (1,800 U/L) were obtained for aeration rates of 3.0 L air/min, with a sharp reduction in both when the aeration rate was up to 4.0 L air/min [29].…”
Section: Influence Of Oxygen Transfermentioning
confidence: 99%
“…In the rest of the studies, the cells that were previously cultured in agar plates, were suspended in 0.9% NaCl solution and then added into the flasks containing the fermentation medium [12,17]. Only Sokolovska et al [18] reported that C. cylindracea inoculum was prepared by inoculation of the cells, first in glucose-rich medium and then in the medium containing olive oil. However, no reports appeared in the literature comparing the progress of C. rugosa fermentations carried out in sequential pre-culture and enzyme production media of different compositions with that carried out using only enzyme production medium.…”
Section: Discussionmentioning
confidence: 99%
“…Lipase activity was determined by the method of Sokolovska et al [23] with the following modifications: 0.5 ml crude lipase solution was mixed with 1 ml 50 mM phosphate buffer, pH 7.0, and 1.5 ml tributyrin in 25 ml Erlenmeyer flasks; after 60 min incubation at 37°C the emulsion was mixed with 1 ml acetone:ethanol mixture (1:1) to extract free fatty acids; free fatty acid concentration was determined by titration (0.05 N KOH) using phenolphthalein as an indicator. Controls were carried out as above, but the enzyme solution was inactivated by boiling for 20 min.…”
Section: Assay Methodsmentioning
confidence: 99%